2021
DOI: 10.1007/s10900-021-01030-y
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Healthcare Students in Vietnam to Volunteer During the COVID-19 Pandemic

Abstract: Healthcare students play an important role in volunteering activity, often addressing staff shortages. However, during the COVID-19 pandemic, the willingness of students to volunteer in contribution to the pandemic response, especially in Vietnam, has not been thoroughly investigated. This study aimed to determine the prevalence of and factors associated with the willingness of healthcare students to volunteer during the COVID-19 pandemic in Vietnam. For this, an online cross-sectional survey was conducted, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
2
29
0
4
Order By: Relevance
“…Fourteen studies (34.2%) found a willingness to volunteer ranging from 19.5 to 91.5% ( 32 , 36 ). However, the actual implementation of this willingness was only observed in a lesser proportion (6.5–67.9%) ( 25 , 37 40 ), and their readiness level was still low (18.6–58.6%) ( 32 , 38 , 41 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Fourteen studies (34.2%) found a willingness to volunteer ranging from 19.5 to 91.5% ( 32 , 36 ). However, the actual implementation of this willingness was only observed in a lesser proportion (6.5–67.9%) ( 25 , 37 40 ), and their readiness level was still low (18.6–58.6%) ( 32 , 38 , 41 ).…”
Section: Resultsmentioning
confidence: 95%
“…Nine studies described the types of volunteering activities carried out by health professional students during the pandemic ( 7 , 8 , 22 , 25 , 27 , 39 , 46 48 ). The activities can be broadly divided into nine different categories, defined as hospital works (triage, admission wards, and emergency room) ( 7 , 25 , 27 , 46 ), call center and administration ( 7 , 27 , 39 , 46 ), epidemiological aspects (contact tracing, testing) ( 22 , 47 , 48 ), online or remote consultation (regarding COVID-19 or non-COVID-19 cases, using phone or internet) ( 46 49 ), laboratory-related works ( 47 ), food and/or PPE supply ( 27 , 39 ), mentoring juniors ( 39 ), public education (such as countering hoaxes) ( 48 ), and in research programs ( 8 ). Some students also reported participating in more than one type of volunteering activity ( 7 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, more than half of the students (54.9%) had participated in clinical training during the pandemic, and a greater ratio of participants with clinical practice experience was found in the willingness group than in the unwillingness group. Previous studies have shown that willingness to volunteer during the COVID-19 pandemic was higher in medical students with clinical practice experience than in students without such experience [34]. Additionally, 57.8% of physicians with experience in caring for COVID-19 patients in hospitals were willing to care for patients suffering from COVID-19 [25].…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, 57.8% of physicians with experience in caring for COVID-19 patients in hospitals were willing to care for patients suffering from COVID-19 [25]. It is likely that students participate both directly and indirectly in treating patients during their clinical training [34]. Therefore, healthcare providers with experience in caring for patients during disaster situations are more willing to participate in providing healthcare during future disasters because they have gained evidencebased knowledge and training in disaster management and response strategies [35].…”
Section: Discussionmentioning
confidence: 99%